The Kikuyu Conceptualization of Adoption: A Cognitive Grammar Approach (Impact: Journal of Transformation, 2018)
The process of Bible translation entails interpretation of concepts in the original text. Such interpretation calls upon translators/exegetes not to just reconstruct and analyze the conceptualization evoked by a biblical concept with regard to the conceptual universe of the author and his original recipients but also to analyze the conceptualization evoked with regard to the speakers of a receptor language. The underlying idea is to aid the translator/exegete, in a complementary way, to gain an understanding of the meaning of the original text. The aim of this approach to the translation task is to come up with a translation that is clear to the speakers of a receptor language. This paper concentrates on the concept of ‘adoption’ represented by the Greek term, huiothesia in Gal. 4:5; Rom. 8:15, 23; 9:4; and Eph. 1:5 Which is variously rendered in the English translation versions. Focusing on Kikuyu as a receptor language, the concept of adoption is represented by gũciarwo na mbũri ‘to be procreated by means of (slaughtering) a goat’ the Kikuyu label for adoption. The evoked conceptualization is analyzed using a Cognitive Grammar approach. Cognitive Grammar enables first the semantic characterization of the expression gũciarwo na mbũri and its components as grammatical constructions, second the analysis of the conventional conceptual content evoked by gũciarwo na mbũri and its components in the conceptual universe of the Kikuyu speakers. The evoked conceptual content is incorporated in the emergence of the meaning of the expression.